PERLINDUNGAN HUKUM TERHADAP KONSUMEN DALAM PERJANJIAN BERLANGGANAN LAYANAN INTERNET - Rahmayani, Dina; Syuryani (Collegium Studiosum Journal, 2024)
Internet has become a fundamental necessity for modern society today. Shopping, sending emails, listening to music, and advertising products can all be done through the internet. To facilitate telecommunications, there is a need for a managing body that provides internet services, one of which is carried out by PT. A, which operates in the field of telecommunications service connections. One of the products offered by PT. A is the internet. more people subscribe, there are also increasing issues related to internet services. These range from technical to non-technical service problems that result in losses for customers. Method used in this research is a conceptual approach, which provides an analytical perspective on legal problem-solving seen from the aspect of legal concepts underlying it and based on internet,con information from internet service users. Based on the results of this research, sumer regarding the implementation of agreements, as well as the rights and protection,a obligations between the company and the customers have the clause agreements made by the company. It's just a matter of been stipulated in greements. understanding for both customers and the company to fulfill and implement rights and obligations so as not to cause breach of contract.